Are You a Designer Bride? Power Relations Between Popular Media and the Indian Bride - Chattaraj, Jhilam (SARE: Southeast Asian Review of English, 2023)
Abstract: In recent years, the bride has become a representative fashion icon of clothing, cosmetic and entertainment industry in India. Designers like Sabyasachi Mukherjee, seem to project the bride’s access to bridal couture as a symbol of empowerment, emancipation and even nationalism. However, statistics would prove that Indian brides still carry the burden of cultural evils like dowry, domestic abuse, psychological pressures of marriage and child-bearing. Television shows like “Band, Baaja, Baraat,” lavish weddings of Bollywood actors like Anushka Sharma and Deepika Padukone have evoked new aspirational images in the imagination of the Indian middleclass. The present paper attempts to question the proliferation of wedding couture as a symbol of power and resistance to power. It aims to explore the route maps of capitalist desire and the seduction of women into this ambiguous role-play; are fashionable brides dressed in hot pants foolish consumers or artful minds who bend patriarchal structures even if for a short time? The paper will be premised on theories of popular culture, post-feminism, everyday feminism and cultural studies. It will enable us to address the reductive approach of contemporary capitalism towards complicated ideas of gender, class, caste, money, religion and region in Indian marriages. It will refer to ideas by Germaine Greer, Gloria Steinman, Stephanie Genz, Maitrayee Chaudhuri, Bharati Chibber, Santosh Desai to investigate into the empowering images of young brides as curated and exhibited by popular media. Key Words: bride, couture, media, feminism, fashion, India